Acute Aortic Insufficiency due to Rupture of an Aortic Valve Commissure. Issue 4 (12th January 2014) - Kassem, Samer; Polvani, Gianluca; Al Jaber, Emad; Gennari, Marco
Abstract Myxomatous degeneration generally involves the atrioventricular valves (mitral and tricuspid). Rarely, it may affect the aortic or pulmonary valve. We report a case of an acute severe aortic insufficiency due to a rupture of a commissure of the aortic valve in a patient who had previously undergone mitral valve surgery for myxomatous mitral valve prolapse. doi: 10.1111/jocs.12276 (J Card Surg 2014;29:497–498)